The first record of Abutilon theophrasti (Malvaceae) in the flora of Libya - Mahklouf, Mohammed Hadi; El-Ahamir, Sh-Hoob Mohammed (Phytotaxa, 2019)
A new record for Abutilon theophrasti is recorded for the first time in the flora of Libya. This widespread agricultural weed was collected from El-Hamra region (El-Qabel) in the Nafusa Mountain south of Tripoli. To facilitate further identification and future detection, a full description, habitat information, distribution map and distribution data are provided. A brief discussion about the most important threats posed by this species is presented.